Software based agricultural monitoring with the integration of sensor technology - Seyyed Najafi; Dragan Marinkovic; Nenad Komazec (Computational Algorithms and Numerical Dimensions)
This study investigates how the current academic literature discusses Wireless Sensor Network (WSN) applications in agriculture. The WSN is widely used to build decision support systems to overcome many problems in the real world. Using the basic principles of Internet and WSN technology, precision agriculture systems based on the Internet of Things (IoT) technology are explained in detail, especially on the hardware architecture, network architecture, and software process control of the precision agriculture system. The software monitors data from the wireless sensors, but implementing a WSN will optimize the usage of water fertilizers and maximize crop yield. Nowadays, the climatic conditions are not the same and predictable. There are many ways to cultivate healthy crops in a year. But it requires a lot of human resources, which is a burden nowadays. We are designing a WSN  for smart agriculture to make it smart and straightforward and give correct input to the corp.